The impact of academic digital library engagement among postgraduate scholars / Anis Fadilah Zulkifli and Eza Eliana A. Wahid - Zulkifli, Anis Fadilah; A. Wahid, Eza Eliana (Faculty of Information Management, 2024)
Academic Digital Library is a web-based system that provides access to various academic information and services. This article aims to investigate UiTM Digital Library's efficiency in meeting post-graduate students' needs by correlating their satisfaction with the following predictors: technological and individual factors, digital library engagement, and perceived benefits. The questionnaire was developed based on the instruments used by previous researchers. An online questionnaire was distributed to UiTM Selangor post-graduates, obtaining a sample of 341 respondents. The results of this study indicate that postgraduate students were aware of digital reference services offered by an academic library. The finding also revealed the level of usage and satisfaction regarding digital reference services. The result of this study will enable library management to recognize the usage of digital reference services among students. The findings will help address libraries and encourage students to use digital reference services to seek information effectively and efficiently.